PENGEMBANGAN MEDIA FLIPBOOK BERBASIS REALISTIC MATHEMATICS EDUCATION PADA KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Karsim, Karsim; Ratnaningsih, Nani; Rahayu, Diar Veni (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
Teacher’s lack of interactive learning media and abstract mathematics learning materials results in low mathematical communication skills as indicated by students' answers in solving math problems. Flipbook media is one of the interactive and interesting learning media in learning mathematics which accommodates the principles of the Realistic Mathematics Education (RME) approach. This study aims to determine the procedure for developing RME-based flipbook media and to determine students' mathematical communication skills after using the media developed on circle material. This type of research is R & D (Research & Development) research using the 4D development model (Define-Design-Develop-Disseminate). The subjects in this study were 3 mathematics teachers, 6 students taken from each class VIII outside class VIII-E, 2 material experts, 2 media experts and 32 students from class VIII-E SMPN 3 Banjar. Data collection techniques are observation, interviews, questionnaires and tests. The data analysis technique used is descriptive statistical analysis and qualitative data analysis. Based on the analysis of the results of the mathematical communication ability test, as many as 31.25% of students showed a level of mathematical communication ability in the "high" category, as many as 43.75% of students showed a level of mathematical communication ability in the "medium" category as many as 25% of students shows the level of mathematical communication skills in the "low" category. It can be concluded that RME-based flipbook learning media is feasible and effective in students' mathematical communication skills. This research is a reference for teachers to make flipbooks using Flip PDF Professional software which can assist the learning process and further researchers can conduct research and development of flipbooks in collaboration with other software on different material and mathematical abilities